HISTORICAL PHILOSOPHICAL STUDY OF THE DEVELOPMENT OF THE ANCIENT TURAN CULTURE - Khudоyаrоv Jаsur Sаpаrоvich (Innovate Conferences, 2025)
A historical and philosophical study of the development of ancient Turanian culture includes an in-depth analysis of the Turkic peoples living in this region, their social, economic and cultural life, as well as their philosophical thoughts. This study examines the cultural heritage, mythology, art and philosophical views of Turan in ancient times. It shows how the peoples of Turan developed through mutual contacts, trade routes and cultural exchanges. In particular, the interactions with other cultures through the Silk Road and their results are studied. The philosophical foundations of ancient Turanian culture are examined in connection with views on the existence of humanity, the relationship between nature and society. This study sheds light on how Turanian culture was formed in a historical context and how it is necessary to preserve its heritage in the modern world.
Keywords: Ancient Turan, Culture, Philosophy, Historical development, Mythology, Art, Trade routes, Cultural exchange, Humanity.